Age as a determinant of emotional health problems among secondary school teachers in Ilorin Metropolis - Lasisi, Adekola Kamil; Annor, Patricia Omioguele (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
The study examined age as a determinant of emotional health problems among secondary school teachers in Ilorin Metropolis. The study adopted a descriptive survey of a correlation type. The researcher's instrument titled the Emotional Style Questionnaire from Kesebir et al. was used to collect the data for the study. The reliability coefficient of the questionnaire was reported to be 0.85. There was no significant relationship between ages and emotional health of secondary school teachers in Ilorin Metropolis; there was no significant relationship between ages and emotional health of younger secondary school teachers in Ilorin Metropolis; and there was no significant relationship between the ages and emotional health of older secondary school teachers in Ilorin Metropolis were postulated hypotheses of the study. These hypotheses were tested at a 0.05 level of significance. Pearson-Product Moment Correlation was the statistical method employed for this study. The finding of the hypotheses showed there were significant relationships between the ages and emotional health of secondary school teachers in Ilorin Metropolis. There was a significant relationship between the ages of young teachers and their emotional health in Ilorin Metropolis of Kwara State. It was also observed that there was a significant relationship between the ages of older teachers and their emotional health in the Ilorin Metropolis of Kwara State. The study recommended that counsellors should orientate teachers on how to maintain good emotional health irrespective of their age and gender.